Training periodization - what is it? - Arbeit, E. (2007)
This article on training periodization, written from the perspective of biological rhythms, was presented by the author at the 2007 International Throws Conference held in Windsor, Ontario, Canada September 29th and 30th, 2007. In the previous two, three years there was started from different sport scientists as well as coaches the attempt, to define new the contents of training periodization. Several of these attempts the author of this article means that this publications are not helpful for the practice of elite sports, especially for training processes with high performance athletes. More or less all authors of these articles refer their own position to the theoretical positions of Matwejew, L.P. (1973,1981,1983). Matwejew goes for the sport scientist, who created the scientific basis of training periodization. The author of the present article refers emphasize particularly on the positions of Matwejew, especially because he was translating his often quoted standard textbook: "Basis of Sports Training" from Russian into the German language. But since the publications of Matwejew are more than 25 years passed. Years in which the world of elite sports was changing totally. What means periodization of a training process? "Periodization" that means the objective necessary time-structure of the training process for the preparation of a competition series or a main competition. Periodization of a training year is depending from four criteria: 1. The competition calendar with the dates of the main competitions; In the training year 2007/2008 the indoor World Championship in March and the Olympic Games in August; 2. The biological rhythm of the human organism 3. The dynamic of adaptation; 4. The stages of the stimulus -effect of training exercises and training loads in the context of the development of the performance-structure and the time to build-up the shape for competitions.